2004
DOI: 10.1346/ccmn.2004.0520203
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermal Stability of Organically Modified Layered Silicates

Abstract: Bromide-containing impurities were found to decrease the thermal stability of quaternary alkyl ammonium-modified layered silicates. Improved purification procedures completely removed bromide and led to a 20ºC to >100ºC increase in organic modified layered silicate thermal stability. Using mass spectrometry and thermal and electrochemical analysis, N,N-dimethyl-N,N-dioctadecyl quaternary ammonium-modified montmorillonite and fluorinated synthetic mica were found to degrade primarily through elimination and nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 10 publications
(13 reference statements)
6
35
0
1
Order By: Relevance
“…It was also stated that the onset temperature was independent of factors such as architecture (dimethyl cf trimethyl substitution on the quaternary group); exchanged ratio or preconditioning such as washing. However other studies have shown that bromide-containing impurities decreased the thermal stability of alkylammonium organoclays and removing these led to an increase of degradation onset temperature of more than 100°C [18]. As it has been shown that weight loss around 155°C is due to water desorption [17] the onset degradation in this paper was defined as the temperature above 170°C…”
Section: Resultsmentioning
confidence: 93%
“…It was also stated that the onset temperature was independent of factors such as architecture (dimethyl cf trimethyl substitution on the quaternary group); exchanged ratio or preconditioning such as washing. However other studies have shown that bromide-containing impurities decreased the thermal stability of alkylammonium organoclays and removing these led to an increase of degradation onset temperature of more than 100°C [18]. As it has been shown that weight loss around 155°C is due to water desorption [17] the onset degradation in this paper was defined as the temperature above 170°C…”
Section: Resultsmentioning
confidence: 93%
“…The extra surfactant influences the organoclay properties and, as a consequence, those of the resultant polymer nanocomposites [27][28][29]. The excess unbound surfactant can be effectively removed by appropriate solvent washing procedures [18,30]. In this paper we tested the efficiency of toluene and ethanol washing.…”
Section: Resultsmentioning
confidence: 99%
“…10.2 shows that the alkylammonium ions intercalated between the clay layers, decompose to volatile compounds in more than one step and in a larger temperature range (e.g. 200-500°C) [10,11,[17][18][19]. These differences are explained by the interaction clay-organic compound and they help in understanding the thermal behaviour of clay-organic polymer nanocomposites.…”
Section: Thermal Degradation Of Clays and Organoclaysmentioning
confidence: 99%
“…The first event of decomposition is usually due to the unconfined fraction of alkylammonium, that consists of alkylammonium surfactant which has not undergone the ion exchange reaction and is either complexed on the outer surface of the clay or within void spaces between primary particles or inside the interlayer space but in a peripheral position [10,[17][18][19]. This behaviour shows that the Lewis and/or Brønsted acid sites behave as catalytic sites affecting the initial stage of decomposition of the alkylammonium molecules accelerating the carbon-carbon bond scission at high temperature.…”
Section: Thermal Degradation Of Clays and Organoclaysmentioning
confidence: 99%